Formation of the creative personality of a child of preschool age by means of artistic word - Kurchatova, Angelika (ScienceRise: Pedagogical Education, 2017)
The topicality of the chosen topic of the research is proved by the important role of fiction in the formation of the creatively directed personality of a preschool child, his/her creative abilities. There were elucidated the features of formation of the creative personality of a preschool child by means of artistic word. There were created creative tasks for the formation of the creative personality of a pre-school child by means of artistic word. In the study was proved that the development of artistic activity, directed on the formation of the creative personality of a child is provided due to the creation of favorable conditions: organized purposeful work in the given direction that includes a series of creative tasks with an element of novelty; interested attitude of an educator to the child creativity. The conclusion was made about the fact that the use of diverse creative tasks in the learning-upbringing process favors the development of the creative potential of preschool children. Making acquainted with fiction, a teacher leads children to the analysis of a work, teaches to understand its content, familiarizes them with genre, compositional, speech features of different works. Children use obtained literature knowledge in own creativity, at composing stories. As a result of the realized work, most children form schemes independently, select symbolic signs, and author stories, tales, verses were created on their base